A Novel Combined Use of Dupilumab for Treatment of Aggressive Refractory Pemphigus Vulgaris Complicated With Pulmonary Tuberculosis: A Case Report and the RNA-seq Analysis - Chen, Siji; Zhan, Shaowei; Hua, Chunting; Tang, Yi; Cheng, Hao (Frontiers in Immunology, 2022)
Background: Pemphigus vulgaris (PV) is a kind of IgG-mediated autoimmune blistering disease (AIBD) that is characterized by loss of keratinocyte adhesion in the epithelium of mucous membranes or skin. Recently, pemphigus vulgaris was thought to be associated with classical T helper 2 (TH2)-type cytokines such as interleukin‐4 (IL-4). A humanized monoclonal IgG4 antibody called dupilumab binds to the alpha subunit of the interleukin‐4 receptor (IL‐4Rα) and inhibits the signaling of interleukin‐4 (IL-4) and interleukin‐13 (IL-13), which has been successfully applied for atopic dermatitis and asthma. Recently, this biological agent has been approved for cutaneous autoimmune bullous diseases such as bullous pemphigoid. Objective: To determine whether dupilumab may be of benefit in the aggressive refractory pemphigus vulgaris. Methods: We report a 35 years old male with refractory pemphigus vulgaris and pulmonary tuberculosis (TB) who received treatment with dupilumab for 10 weeks. The mRNA expression of peripheral blood mononuclear cells (PBMCs) was analyzed by RNA sequencing (RNA-seq) before and after medication administration, which showed the efficacy of these agents. Results: The skin lesions of the patient improved in response to the combined use of dupilumab, moderate dose of glucocorticosteroids, and intravenous immune globulin (IVIG). Down-regulations of inflammation response-related genes and IL4-related genes were observed in PBMCs. Conclusion: Our results suggest that a combination of high dose IL‐4Rα antagonist dupilumab, glucocorticosteroids and IVIG. Dupilumab may provide a systemic treatment of aggressive refractory pemphigus vulgaris.